Juridical Review of Internal Control System Design in Regional Financial Management in Indonesia - Prawira, Suwiryo (Journal of Legal Contemplation, 2025)
This study examines the design of an internal monitoring system for regional financial management at the regional level “Ius Constitutum”. The design of an internal regional financial supervision system regulated in various regulations is expected to produce effective regional financial management. However, with the recent rise in acts of budget misuse and fraudulent regional financial reporting, this certainly leaves new work for policy makers to review the existing internal monitoring system. The main objective of this study is to find out whether the internal control system model that has been established is able to guarantee the implementation of effective regional financial administration, or is it the opposite. With various incidents occurring regarding irregularities in the implementation of regional budgets, this study then describes the weaknesses and efforts to optimize the regional financial internal monitoring system.  This research uses a normative legal research method that relies on a statutory approach and a conceptual approach. The research results show that there are still weaknesses in the design of the internal supervision system in regional financial management. This can be seen from the regulation of the internal supervision system which is not yet optimal because it still opens up room for compromise between supervisory officials and regional heads. In addition, the design regarding the position of regional inspectorates in the applicable regulations does not allow Government Internal Audit Apparatus to act independently in carrying out their supervisory duties. This study is encouraging  to make improvements to the position of the regional Inspectorate through  revision of existing regulations. The position of the internal regional inspectorate implementation  Internal supervision must be interpreted within the scope of internal supervision in the sense  broad.